Channels of Research Dissemination to Reach End-User Targets - Maria EGGINK (Communications of International Proceedings, 2020)
Dissemination of research is important in order to justify the research expenses and to reach the intended goals of the research. Unfortunately, the findings of research do not always reach the intended end-user and the expenses are often fruitless. The aim of the research is to determine how the research findings of university researchers can reach the end user in order to ensure a return on investment, monetary or otherwise. Secondary data was used and a literature study was conducted to determine the current dissemination practices. Research repositories were reviewed as a proposed channel for research dissemination that is more accessible to end-users. It was found that the more popular dissemination channels were not necessarily the best channels that to reach the intended target. It is proposed that universities consider the establishment or improvement of institutional repositories in order for research findings to reach wider communities and end-users.
Keywords: Research Dissemination; Institutional Research Repositories